Implementation of Socio-Scientific Issues (SSI) in Improving Chemical Literacy of Senior High School Students: A Systematic Literature Review - Ruth Tamarista Nadapdap; Tiona Christian Br Silitonga; I Wayan Redhana (Universitas Lampung, 2026)
Implementation of Socio-Scientific Issues (SSI) in Improving Chemical Literacy of Senior High School Students: A Systematic Literature Review. This systematic literature review aims to analyze the implementation of the Socio-Scientific Issues (SSI) approach in senior high school chemistry learning and its impact on improving students’ chemical literacy. The review followed the PRISMA guidelines by analyzing 20 peer-reviewed national and international journal articles published between 2015 and 2025. Relevant studies were selected based on inclusion and exclusion criteria focusing on SSI implementation in chemistry learning and its relationship with students’ chemical literacy. The findings indicate that the SSI approach is implemented through various learning models, including the Learning Cycle 5E, guided inquiry, and project-based learning, using real-world issues such as waste management, environmental pollution, alternative energy, and addictive substances. The implementation of SSI consistently improves students’ chemical literacy in conceptual, epistemic, and affective dimensions. In addition, SSI-based learning enhances critical thinking skills, scientific argumentation, evidence-based decision making, and social awareness. Learning media such as SSI-based modules and e-modules are reported to be valid, practical, and effective in increasing students’ motivation and active participation. However, several challenges remain, particularly related to teachers’ readiness, limited instructional time, and the availability of contextual learning resources. Overall, the SSI approach is effective in fostering multidimensional chemical literacy and supporting context-based chemistry learning aligned with 21st-century educational goals. Further research is recommended to explore more diverse SSI contexts and to develop comprehensive chemical literacy assessment instruments.